USE OF АNATOMY TABLE IN STUDYING INDIVIDUAL FEATURES OF ARTERIAL NETWORK OF ELBOW JOINT - O. V. Murashov (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова)
The article represents a description of the individual features of the arterial network of the elbow joint and comparing results of the investigation with data of Russian and foreign anatomical schools of the USA, Canada, India and Great Britain. The investigation of the arterial network of the elbow joint of two male and two female dead bodies was implemented on the basis of the Anatomy Table. The screenshots was taken after extracting the arteries of this area. The graphic figures allowed to identify individual features of the arterial network of the elbow joint.